A friendly dialogue between an atheist and a Christian - Palau, Luis, 1934-2021.; Qizheng, Zhao, 1940- (Grand Rapids, Mich. : Zondervan, 2008)
"In A Friendly Dialogue between an Atheist and a Christian, Luis Palau, representing the Christian faith, and Zhao Qizheng, representing atheism, present a composite of recorded dialogues held in China in 2005 between them. Through these dialogues, readers are provided insight into the current struggles atheists have regarding the truth claims of the Christian faith. Topics discussed include philosophy, history, religion, the Bible, creation, atheism, Confucianism, politics, ethics, Chinese and Western cultures, and the relevance of Jesus Christ to society. Through the engaging dialogue between Luis Palau and Zhao Qizheng, many of the stereotypes and misinformation concerning the Chinese culture are exposed, revealing a nation in which the Bible is published and new churches are being built. By avoiding the use of complicated theological language, these discussions express the concerns of both Christians and atheists in a clear, meaningful, and respectful way. A Friendly Dialogue between an Atheist and a Christian is a must read for anyone interested in gaining a greater appreciation of the oriental world of China and how the Christian faith is being received within that context."--Publisher description.
On the Bible and God -- On the creation -- On religion and the spirit -- On religious beliefs in China -- On Chinese and western cultures and philosophy -- On religion and science -- On religion and social harmony.
Previously published: 1st ed. Riverside talks. Beijing, China : New World Press, 2006.
Keywords: Christianity and atheism